Reading, Writing, and Literacy 2.0 Teaching with Online Texts, Tools, and Resources, K-8 - Denise Johnson (International Reading Association, Newark, DE, 2014)
In today's high-stakes testing environment, integrating technology into the curriculum is often seen as something ''extra'' or for use with a few special projects. With the growth in Internet use by even the youngest children, educators urgently need a practical introduction to online literacy and reading comprehension. Reading, Writing, and Literacy 2.0 offers that and more by providing tools and teaching strategies for incorporating online reading and writing into classroom learning, as well as a host of web resources that teachers can draw on to make this happen. All this without endless hours of searching! Denise Johnson's book connects to the Common Core State Standards and is organized around the Technological Literacy Assessment of the National Assessment of Education Progress (NAEP), which focuses on three areas that characterize a technologically literate person: knowledge, capabilities, and critical thinking and decision making. This resource provides everything reading teachers need to begin using technology to deepen and enrich literacy learning for all students. In addition, the author maintains a companion blog to update and add helpful teaching links.
Keywords: compréhension; éducation; jeunesse; lecture numérique; littératie numérique